In-season monotony, strain and acute/chronic workload of perceived exertion, global positioning system running based variables between player positions of a top elite soccer team - Oliveira, R.; Martins, A.; Nobari, H.; Nalha, M.; Mendes, B.; Clemente, F. M.; Brito, J. P. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background The interpretation of the load variations across a period seems important to control the weekly progression or variation of the load, or to identify within- micro and mesocycle variations. Thus, the aim of this study was to describe the in-season variations of training monotony, training strain, and acute: chronic workload ratio (ACWR) through session rating of perceived exertion (s-RPE), total distance and high-speed running (HSR) according to playing positions in an elite soccer team.